Orbital Cavernous Hemangioma Presenting with a Dome-Shaped Maculopathy-Like Appearance on Swept-Source Optical Tomography Imaging - Şükran Bekdemir; Ahmet Kaan Gündüz; Cevriye Cansız Ersöz (Case Reports in Ophthalmological Medicine)
A 43-year-old patient presented with painless proptosis, limited upgaze, and vision loss in the right eye. Funduscopic examination revealed right optic disc edema and subtle macular compression. Swept-source optical coherence tomography (SS-OCT) revealed a smooth contoured elevation of the posterior pole without any distortion of retinal structures, an appearance closely simulating dome-shaped maculopathy. Swept-source optical coherence tomography angiography (SS-OCTA) revealed normal retinal and choroidal vasculature. Orbital magnetic resonance imaging demonstrated a well-circumscribed intraconal mass compressing the globe and optic nerve in the right orbit. An anterior orbitotomy was performed, whereby the tumor was totally excised and diagnosed histopathologically as cavernous hemangioma. This case represents an orbital cavernous hemangioma touching the eyeball and producing compression of the posterior pole presenting with a dome-shaped maculopathy-like appearance on SS-OCT. SS-OCT and SS-OCTA are important noninvasive tools for evaluating the retinal and choroidal effects in orbital tumors.